2006
DOI: 10.1152/ajplung.00489.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen sulfide in cecal ligation and puncture-induced sepsis in the mouse

Abstract: Endogenous hydrogen sulfide (H(2)S) is naturally synthesized in various types of mammalian cells from l-cysteine in a reaction catalyzed by two enzymes, cystathionine-gamma-lyase (CSE) and/or cystathionine-beta-synthase. The latest studies have implied that H(2)S functions as a vasodilator and neurotransmitter. However, so far there is little information about the role played by H(2)S in systemic inflammation such as sepsis. Thus the aim of this study was to investigate the potential role of endogenous H(2)S i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 31 publications
7
170
1
3
Order By: Relevance
“…Furthermore, PAG prevented the increase in plasma levels of markers of liver and pancreas injury and reduced the tissue content of myeloperoxidase (an index of tissue neutrophil infiltration) (24). In a model of cecal ligation and puncture, PAG treatment reduced tissue neutrophil infiltration and significantly prolonged the survival of the animals (25). PAG is the most widely used in vivo inhibitor of H 2 S production by CSE.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PAG prevented the increase in plasma levels of markers of liver and pancreas injury and reduced the tissue content of myeloperoxidase (an index of tissue neutrophil infiltration) (24). In a model of cecal ligation and puncture, PAG treatment reduced tissue neutrophil infiltration and significantly prolonged the survival of the animals (25). PAG is the most widely used in vivo inhibitor of H 2 S production by CSE.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S has been proposed as a potential endogenous ligand for K ATP channels and induces K ATP channel-mediated vasorelaxation [28] in several vascular tissues, promoting speculation that H 2 S may play a role in endotoxic shock, an important form of acute inflammation, as mentioned. Indeed, early studies using cecal ligation and puncture (CLP) or injection of bacterial LPS into rats or mice significantly increased the expression of CSE and CBS and H 2 S synthesis in plasma, vascular tissues, lung, liver, kidney and pancreas [21,[29][30][31][32]. This suggested that, as with • NO synthesis (via inducible nitric oxide synthase [iNOS]), H 2 S synthesis is also an inducible phenomenon.…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
“…At these plasma concentrations, H 2 S induces K ATP -dependent vasodilatation in anesthetized animals and in isolated aortic rings [28,33,34]. Conversely, administration of the CSE inhibitor propargylglycine (PAG; see later) to LPS-or CLPtreated animals decreased plasma H 2 S levels significantly, tissue edema and increased survival [21,29,30], suggesting that elevated plasma H 2 S was likely to be associated with the hemodynamic collapse observed in septic shock [21]. It should be noted that the protective effects of PAG may be independent of the improvement of hemodynamics (or CSE), since PAG treatment alone did not alter systemic blood pressure or affect LPS-induced hypotension but did significantly reduce the hepatic, pancreatic and neuromuscular damage induced by LPS [31].…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
“…25 For example it has been reported that the plasma H 2 S concentration, and CSE expression and activity are increased in lipopolysaccharide-treated mice 23 and in a cecal ligation and puncture model of sepsis in the mouse. 61 The findings of the latter study imply that H 2 S enhances the inflammatory response and end organ damage associated with sepsis. For example, in a mouse lung and liver model of sepsis, the CSE inhibitor compound DL-propargylglycine was shown to attenuate the inflammatory response, indicated by a reduction in myeloperoxidase activity, a marker of neutrophil infiltration.…”
Section: Pro-and Anti-inflammatory Actions Of H 2 Smentioning
confidence: 79%
“…PAG was also shown to reduce mortality after caecal ligation and puncture. 61 The mechanism through which H 2 S exerts these pro-inflammatory actions in vivo is unclear.…”
Section: Pro-and Anti-inflammatory Actions Of H 2 Smentioning
confidence: 99%